Comparative genomics highlights symbiotic capacities and high metabolic flexibility of the marine genus pseudovibrio - Versluis, Dennis; Nijsse, Bart; Naim, Mohd Azrul; Koehorst, Jasper J.; Wiese, Jutta; Imhoff, Johannes F; Schaap, Peter J; van Passel, Mark W J; Smidt, Hauke; Sipkema, Detmer (Oxford University Press, 2018)
Pseudovibrio is a marine bacterial genus members of which are predominantly isolated from sessile marine animals, and particularly sponges. It has been hypothesized that Pseudovibrio spp. form mutualistic relationships with their hosts. Here, we studied Pseudovibrio phylogeny and genetic adaptations that may play a role in host colonization by comparative genomics of 31 Pseudovibrio strains, including 25 sponge isolates. All genomes were highly similar in terms of encoded core metabolic pathways, albeit with substantial differences in overall gene content. Based on gene composition, Pseudovibrio spp. clustered by geographic region, indicating geographic speciation. Furthermore, the fact that isolates from the Mediterranean Sea clustered by sponge species suggested host-specific adaptation or colonization. Genome analyses suggest that Pseudovibrio hongkongensis UST20140214-015BT is only distantly related to other Pseudovibrio spp., thereby challenging its status as typical Pseudovibrio member. All Pseudovibrio genomes were found to encode numerous proteins with SEL1 and tetratricopeptide repeats, which have been suggested to play a role in host colonization. For evasion of the host immune system, Pseudovibrio spp. may depend on type III, IV, and VI secretion systems that can inject effector molecules into eukaryotic cells. Furthermore, Pseudovibrio genomes carry on average seven secondary metabolite biosynthesis clusters, reinforcing the role of Pseudovibrio spp. as potential producers of novel bioactive compounds. Tropodithietic acid, bacteriocin, and terpene biosynthesis clusters were highly conserved within the genus, suggesting an essential role in survival, for example through growth inhibition of bacterial competitors. Taken together, these results support the hypothesis that Pseudovibrio spp. have mutualistic relations with sponges.